2023
DOI: 10.3390/su15076149
|View full text |Cite
|
Sign up to set email alerts
|

Improving Communication of the UK Sustainable Healthy Dietary Guidelines the Eatwell Guide: A Rapid Review

Abstract: Background: Food-based dietary guidelines (FBDG) are a key public health tool, providing evidence-based recommendations for a healthy and more environmentally sustainable diet. Current adherence to national FBDG in the UK is poor with only 0.1% of the population meeting all of the recommendations set out in the Eatwell Guide. Communication of the Eatwell Guide is one of the many essential strategies needed to improve adherence and to support the necessary shift towards sustainable diets in the UK. An effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 99 publications
0
2
0
1
Order By: Relevance
“…Given adopting dietary change is complex and multifactorial (61), public health messaging (alongside policy changes to ensure affordability) focusing on increasing fruit and vegetable intake as the one food group consistently associated with better health outcomes may be a sensible approach. A rapid review of the EWG has suggested a number of recommendations for better communication of the tool which, if adopted, may result in better adherence to the dietary guidelines (62).…”
Section: Discussionmentioning
confidence: 99%
“…Given adopting dietary change is complex and multifactorial (61), public health messaging (alongside policy changes to ensure affordability) focusing on increasing fruit and vegetable intake as the one food group consistently associated with better health outcomes may be a sensible approach. A rapid review of the EWG has suggested a number of recommendations for better communication of the tool which, if adopted, may result in better adherence to the dietary guidelines (62).…”
Section: Discussionmentioning
confidence: 99%
“…Umjesto toga, održiva prehrana (bilo gdje, a ne samo na Sredozemlju) može biti uspješna samo ako uzme u obzir trenutne prakse stanovništva i prilagodi ih budućnosti, prema održivijem modelu koji proizlazi iz mogućnosti lokalnog okruženja i tradicija, a pritom ne zanemaruje trenutne okolnosti, ukuse i težnje svojih populacija. Komunikacija, uključujući onu vlada i međunarodnih organizacija, nedvojbeno će imati utjecaja na uspješnost tih pomaka prema održivijim prehranama ( Johnston et al 2014;Culliford, Bradbury i Medici 2023). Međutim, teme kao što su održiva prehrana i problemi suvremenih prehrambenih sustava su kompleksne, a publika je raznolika.…”
Section: Cum Grano Salisunclassified
“…Communications, including those from governments and international bodies, will undoubtedly have an influence on how successful these shifts towards more sustainable diets will be ( Johnston et al 2014;Culliford, Bradbury, and Medici 2023). Messaging about topics, such as sustainable diets, and the issues around contemporary food systems, however, are complex, and the audiences diverse.…”
Section: Ana Tominc Queen Margaret University Edinburghmentioning
confidence: 99%
“…Consumer-facing dietary guidance must not overburden citizens with overwhelming detail; being concise is critical to the real-life use of guidelines (Webb & Byrd-Bredbenner, 2015). A recent review of communication strategies of the UK Eatwell Guide reinforced this, concluding that language within dietary guidelines should be short, simple, specific and easy to understand (Culliford et al, 2023).…”
Section: Food-based Dietary Guidelinesmentioning
confidence: 99%